Thermodynamic aspects of the development of inhibitory methods of protecting steel from corrosion in salt water environments - Ледовських, В.М.; Левченко, С.В. (Proceedings of National Aviation University (archive), 2008)
The thermodynamics aspects of steel in water-salt solutions spontaneous corrosion and ways of purposeful creation of inhibition methods for its slow-down were considered. For the system Fe-H2O on the basis of diagram Pourbe analysis were determined definite ranges of potentials of metal and pH of the solutions for which corrosive destruction speed reduction were achieved. It is shown that the effective corrosion protection of steel can be achieved by means of measures which include application of inhibitors with simultaneous medium pH modification, as a result there takes place a transition of metal into a stable passivated state. Potentiostatic research of steel in water-salt solutions corrosion had confirmed efficiency of the method offered.